2021
DOI: 10.1016/j.phymed.2020.153390
|View full text |Cite
|
Sign up to set email alerts
|

Shufeng Jiedu, a promising herbal therapy for moderate COVID-19:Antiviral and anti-inflammatory properties, pathways of bioactive compounds, and a clinical real-world pragmatic study

Abstract: Background Shufeng Jiedu capsules (SFJDC), a patented herbal drug composed of eight medicinal plants, is used for the treatment of different viral respiratory tract infectious diseases. Based on its antiviral, anti-inflammatory and immunoregulatory activity in acute lung injury, SFJDC might be a promising candidate for the treatment of COVID-19. Purpose To evaluate the antiviral and anti-inflammatory properties and to discover the mechanism of action of SFJDC as a poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 25 publications
0
71
0
Order By: Relevance
“…Following reports of good clinical efficacy, several TCMs were officially endorsed for clinical use in China and were adopted as part of the treatment plan for COVID-19 [ [31] , [32] , [33] ]. An increasing number of clinical and experimental evidences have proved that TCMs inhibit viral replication owing to specific active ingredients [ [34] , [35] , [36] ]. Herein, we retrospectively analyzed 123 COVID-19 patients who received a combination of western and Traditional Chinese Medicines from the hospitals in Guizhou Province, China.…”
Section: Introductionmentioning
confidence: 99%
“…Following reports of good clinical efficacy, several TCMs were officially endorsed for clinical use in China and were adopted as part of the treatment plan for COVID-19 [ [31] , [32] , [33] ]. An increasing number of clinical and experimental evidences have proved that TCMs inhibit viral replication owing to specific active ingredients [ [34] , [35] , [36] ]. Herein, we retrospectively analyzed 123 COVID-19 patients who received a combination of western and Traditional Chinese Medicines from the hospitals in Guizhou Province, China.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Xia et al found that Shufeng Jiedu capsules can reduce the activity of NFκB in the lungs of HCoV-229E mice. Its active components, wogonin, quercetin, and polydatin, bind directly to the SARS-CoV-2 M pro [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“… anti-inflammatory, anti-SARS-CoV-2 MAPK14, TNF, IL-6, IL-10, PTGS2, etc. 100 fever, dry cough, fatigue, lung CT 88.0% [ [50] , [51] , [52] ] LHQW 13 herbs, including Forsythia suspensa, Lonicera japonica, Ephedra sinica Stapf, Prunus armeniaca L, Isatis indigotica Fort, etc. neochlorogenic acid, amygdalin, prunasin, forsythoside I, rutin, forsythoside A, etc anti-SARS-CoV-2, anti-inflammatory, IL-6, TNF, MAPK1, IL-1B, MAPK8 122 fever, cough, sputum, polypnea, fatigue, anorexia 98.0% [ 53 , 54 ] HXZQ 10 herbs, including Areca catechu L, Angelica dahurica, Perilla frutescens, Pinellia ternata, Atractylodes macrocephala, etc.…”
Section: Role Of Tcm In Covid-19 Treatmentmentioning
confidence: 99%
“…confirmed that SFJD significantly reduces the virus load in the lung from 1109.29 ± 696.75 to 0 ± 0 copies/mL, decreases levels of inflammatory factors (IL-6, IL-10, TNF-α, and IFN-γ), and increases amount of CD4+ and CD8+ cells in the blood, compared to the model group. Importantly, Quercetin, wogonin, and polydatin could directly bind to the key protease of SARS-CoV-2 [ 52 ].…”
Section: Role Of Tcm In Covid-19 Treatmentmentioning
confidence: 99%